Strategi Pemberdayaan Kepemudaan GP Ansor Kelurahan Kunden Kecamatan Wirosari Kabupaten Grobogan - Novian Krisna Jati,; Bastomi, Hasan (Islamic Management and Empowerment Journal, 2025)
The issue of community empowerment is not only run by the government, but also by youth organizations. This research aims to find out the strategies as well as the supporting and inhibiting factors of community empowerment faced by GP Ansor in Kunden Village, Wirosari Sub-district, Grobogan Regency. This research uses field research method with qualitative approach. The data collection techniques used were interviews and observations as well as documentation from several previous studies. The result of this research can be concluded that the strategy of community empowerment by GP Ansor Kunden is implemented in several work programs such as PKD, Ramadan Safari, Inter-religious cooperation and Madrasah Al-Qur'an. As well as several supporting and inhibiting factors for community empowerment activities that come from internal and external to the Kunden community